Molecular insights into methane hydrate growth in the presence of wax molecules. (15th September 2022) - Liao, Qingyun; Shi, Bohui; Song, Shangfei; Duan, Xu; Yang, Fengrui; Gong, Jing
Highlights: Attraction of adjacent wax molecules hinders the diffusion of methane molecules. Adsorbed wax molecules promote hydrate formation at the oil–water interface. Crystallized wax occupies free space for methane molecules mass transfer. Molecular structure and content of the wax govern hydrate growth pathway. Abstract: As a key issue emerged in the exploitation of deep-water oil and gas resources, the natural gas hydrates growth kinetics in waxy oil–water systems is still ambiguous. The microscopic mechanism of how wax affects hydrate growth needs to be elucidated. Molecular dynamics simulations were performed to explore the effect of wax molecules on methane hydrate growth in waxy oil–water-hydrate systems. The simulation results indicated that the different growth pathways of methane hydrate with wax molecules should be attributed to the changes in the mass-transfer process of methane molecules and the structural properties of interface water molecules. When n-heptadecane wax molecules (C17 H36 ) were adjacent to oil–water interface, they inhibited hydrate growth by adsorbing methane molecules in the oil phase and preventing methane molecules from migrating to the water phase. The addition of methyl heptadecanoate wax molecules (C18 H36 O2 ) extended hydrate growth time to achieve a greater amount of hydrate formation by promoting the conversion of the water film between hydrate phase and oil phase into hydrate. In terms of the influence of wax crystallization, the co-crystallization of C17 H36 and C18 H36 O2 hindered the mass transfer of methane molecules at the oil–water interface, which is due to the free space reduction after wax adsorption and the repulsive force between C18 H36 O2 and methane molecules, thereby slowing down the growth rate of hydrate. The dispersed C17 H36 slowed down hydrate growth rate, while the dispersed C18 H36 O2 had almost no effect on hydrate growth rate. Thence, the microscopic analysis based on molecular dynamics simulations indicated that the effect of wax molecules on methane hydrate growth was complex, depending on the specific wax molecular structure and content of the wax.